P474 The value of PCR-based azole resistance detection in invasive aspergillosis: A prospective multicenter study. (20th September 2022) - Huygens, Sammy; Dunbar, Albert; Buijl, Jochem; Maertens, Johan; Verweij, Paul; Klaassen, Corne; Lagrou, Katrien; Van Dijk, Karin; Mercier, Toine; Schauwvlieghe, Alexander; Rijnders, Bart
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM:   Objectives: Prompt detection of azole-resistant Aspergillus fumigatus will result in the timely start of active treatment and may improve the survival of invasive aspergillosis (IA). The use of a multiplex polymerase chain reaction (PCR) targeting Aspergillus species and fumigatus DNA as well as the two most prevalent azole resistance- associated mutations (RAMs) in the cyp51A gen (TR34/L98H and TR46/Y121F/T289A) could shorten the time to detect azole-resistant IA. Methods: In a prospective study in 12 Dutch and Belgian centers, we evaluated the clinical value of the multiplex AsperGenius®PCR in hematology patients with a pulmonary infiltrate undergoing bronchoalveolar lavage (BALf) sampling. The primary endpoint was antifungal treatment failure in the 6 weeks after antifungal treatment initiation in the patients in which azole-resistant IA was detected. Treatment failure was defined as death or a switch to an antifungal agent from another class after at least 5 days of first-line therapy. Patients with a mixed azole-susceptible/resistant infection were excluded from this analysis to ascertain that the infection was indeed caused by the resistant strain. Results: Of 323 patients enrolled, sufficient BALf for PCR testing remained in 299. Probable fungal disease was diagnosed in 95 (34%), Aspergillus cultured in 24 (8%), Aspergillus DNA detected in 118 (39%), and A. fumigatus DNA in 88 (29%) patients. The resistance PCR was conclusive in 54/88 (61%) and RAMs were detected in 8 (15%), Table 1. All 8 had probable IA but 2 had a mixed infection and were excluded. In the 6 remaining patients, treatment failure was observed in one. Compared with the GM negative patients and despite antifungal therapy, a positive GM test was associated with a 13% higher 6-week overall mortality ( P = .01), Table 2. Surprisingly, the 6-week mortality in the 65 patients who had a positive Aspergillus PCR but a negative GM and culture was not increased compared to those with a negative PCR (PCR + 14% vs. PCR- 16% mortality, P = .68). Conclusions: In patients with an underlying hematological disease and a pulmonary infiltrate, the detection of Aspergillus DNA by PCR on BALf was not associated with increased mortality. The exact place of the Aspergillus PCR in the EORTC-MSGERC invasive fungal infection criteria is therefore uncertain. In 15% of the patients in whom A. fumigatus DNA was present, azole RAMs were detected by PCR. In only 1/6 probable cases of IA with RAMs detected, antifungal treatment failure was observed. Basing the choice of antifungal therapy on the result of a cyp51a resistance PCR may help to reduce the impact of azole resistance on mortality.